The importance of physical and mental health in explaining health-related academic role impairment among college students - Wilks, Chelsey R.; Auerbach, Randy P.; Alonso, Jordi; Benjet, Corina; Bruffaerts, Ronny; Cuijpers, Pim; Ebert, David; Green, Jennifer G.; Mellins, Claude A.; Mortier, Philippe; Sadikova, Ekaterina; Sampson, Nancy A.; et al. (Journal of Psychiatric Research, 2020)
Research consistently documents high rates of mental health problems among college students and strong associations of these problems with academic role impairment. Less is known, though, about prevalence and effects of physical health problems in relation to mental health problems. The current report investigates this by examining associations of summary physical and mental health scores from the widely-used Short-Form 12 (SF-12) Health Survey with self-reported academic role functioning in a self-report survey of 3,855 first-year students from five universities in the northeastern United States (US; mean age 18.5; 53.0% female). The mean SF-12 physical component summary (PCS) score (55.1) was half a standard deviation above the benchmark US adult population mean. The mean SF-12 mental component summary (MCS) score (38.2) was more than a full standard deviation below the US adult population mean. Two-thirds of students (67.1%) reported at least mild and 10.5% severe health-related academic role impairment on a modified version of the Sheehan Disability Scale. Both PCS and MCS scores were significantly and inversely related to these impairment scores, but with nonlinearities and interactions and much stronger associations involving MCS than PCS. Simulation suggests that an intervention that improved the mental health of all students with scores below the MCS median to be at the median would result in a 61.3% reduction in the proportion of students who experienced severe health-related academic role impairment. Although low-cost scalable interventions exist to address student mental health problems, pragmatic trials are needed to evaluate the effectiveness of these interventions in reducing academic role impairment.
CRIS-Team Scopus Importer:2020-02-14
Keywords: College students; Health-related academic role impairment; Mental health; Physical health